Educação inclusiva digital: novas ferramentas curriculares para a aprendizagem na educação básica - Costa, Rosana Soares Gomes (2012)
This scientific investigation is inserted in the following line of research: Community Education, Childhood and Youth (MPE) of this Professional Master Program in Theology. The field of study is the new Digital Information and Communication Technologies, digital inclusion and free software - that brings new perspectives to the learning process at school. Since we live in a contemporaneous society, there are new forms of sociability such as the cyberspace, which have been used in different environments. Therefore, we analyze the cultures, educational processes and skills required at school. In this context, this study aims to understand the theoretical concepts and ways of using the new technologies - in a social and pedagogical approach - in order to promote digital inclusion in the Basic Education. Due to our deep analysis, this work is structured in three parts. In the first one, three pillars are highlighted - citizenship, learning and digital inclusion - aiming a revision of neoliberal postures that have been crystallized in the school activities in the sphere of relations between the global and the local. In the second one, we call attention to the profile of the school protagonists. We do it, firstly, in the light of the analysis of the social formation of the student. Secondly, we take into consideration the new curriculum scenarios arising from the virtual world, with emphasis on the possibilities of the digital technologies. And, thirdly, we aim to deeply analyze theory on educational practices and pedagogical requirements of the emerging universe created and recreated by digital technologies in Basic Education